2018
DOI: 10.1152/jn.00079.2017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of muscle action type on corticospinal excitability and triceps surae muscle-tendon mechanics

Abstract: Valadão, Pedro Frederico, 2012. Effects of muscle action type on corticospinal excitability and triceps surae muscle-tendon mechanics. Department of Biology of Physical Activity, University of Jyväskylä. Master's Thesis in Biomechanics. 105 pp.The present study was designed to investigate corticospinal excitability modulation during maximum isometric and eccentric muscle actions with two different velocities. Moreover, the study aimed to clarify the effect of muscle action type on muscle-tendon mechanical beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 154 publications
(257 reference statements)
1
9
0
Order By: Relevance
“…Furthermore, Duclay et al and Gruber et al showed that ECC contractions elicited greater modulation of corticospinal excitability from supraspinal centers (ie, enhanced motor cortical excitability and reduced spinal excitability) when compared to isometric or CON contractions . By contrast, Valadao et al showed no difference in corticospinal excitability between a single session of maximal isometric contractions and ECC contractions at fast or slow contraction velocities of the triceps surae muscle. The authors did, however, report a significant reduction in the cortical silent period duration following both ECC contraction conditions, when compared to isometric contractions.…”
Section: Introductionmentioning
confidence: 89%
“…Furthermore, Duclay et al and Gruber et al showed that ECC contractions elicited greater modulation of corticospinal excitability from supraspinal centers (ie, enhanced motor cortical excitability and reduced spinal excitability) when compared to isometric or CON contractions . By contrast, Valadao et al showed no difference in corticospinal excitability between a single session of maximal isometric contractions and ECC contractions at fast or slow contraction velocities of the triceps surae muscle. The authors did, however, report a significant reduction in the cortical silent period duration following both ECC contraction conditions, when compared to isometric contractions.…”
Section: Introductionmentioning
confidence: 89%
“…Isotonic movements modify corticospinal excitability, such that excitability tends to be lower during lengthening relative to shortening and isometric contractions (Abbruzzese et al 1994; Gruber et al 2009; Duclay et al 2014), which seems to depend on the amount of Ia afferent feedback (Doguet et al 2017). However, elucidating the direct effect of muscle length-related feedback on the corticospinal tract output during dynamic contractions is challenging due to the influence of postsynaptic control mechanisms (Valadão et al 2018; Barrué-Belou et al 2018), and potential differences in neural drive that can influence neurophysiological responses (Abbruzzese et al 1994; Morita et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Valadão, Kurokawa, Finni, and Avela () have recently reported a reduced neural activation (i.e. MEP/M, CSP and H reflex) of soleus muscle during maximal eccentric plantar flexions when compared with maximal isometric contractions, without differences in mechanical variables (i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Hence, it seems that corticospinal inhibitions that occurred at long muscle lengths during eccentric contractions were not, at least directly, related to the extent of tension generated or fascicle stretching. Valadão, Kurokawa, Finni, and Avela (2018) As previously done by Ando et al (2018), we used two ultrasound probes attached in series to perform wider examination of the muscle architecture. Using this procedure, the width of the total scanned field reached 115 mm (including a 15 mm gap in the middle), which allowed us to scan full-size fascicles.…”
Section: Correlations Between Exercise Measurements and Indirect Markmentioning
confidence: 99%